PENGARUH SERVICE RECOVERY DAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH PADA PT. BANK SULTRA CABANG UTAMA KENDARI - Dzulfikri Azis Muthalib; Abd. Azis Muthalib; Muh. Irfandy Azis; Muh. Israwan Azis (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to determine and explain the effect of service recovery and customer satisfaction on customer loyalty at PT Bank Sultra Kendari Main Branch. The population in this study were all customers at PT Bank Sultra Kendari Main Branch. The research sample was 100 customers at PT Bank Sultra Kendari Main Branch. This study uses multiple linear regression analysis. The results showed that: (1) Simultaneously there is a positive and significant effect of service recovery variables and satisfaction on customer loyalty. This fact shows that the better the service recovery and satisfaction provided, the higher the customer loyalty at PT Bank Sultra Kendari Main Branch. (2) Service recovery variables have a positive and significant effect on customer loyalty. The better the service recovery provided to customers, the higher the customer loyalty at PT Bank Sultra Kendari Main Branch. (3) Customer satisfaction variables have a positive and significant effect on customer loyalty. The better the satisfaction felt by the customer, the higher the customer loyalty at PT Bank Sultra Kendari Main Branch.